גבולות החדר וחיק האם: על ביקורת ספרות הנשים העברית והישראלית - זכאי, אוריאן (מכאן, 2020)
This article traces two major questions in feminist scholarship on Hebrew women's literary writing: first, "question of difference", namely, can "women's literarure" be read as a separate of Hebrew literature that is defined by the gender difference? And second, "the question of continuty", i.e., to what extent can we walk of a Hebrew women's literary tradition, ranging from the emergence of Modern Hebrew literature, the article demonstrates how these two questions are mapped onto the imagined space and time of the  national narrative. Therefore, productive as they are, the "question of difference" and "the question of continuity" often lock the conversation into one axis of analysis - the relations between gender and nation - and obscure its intersections with other categories such as ethnicity and class in shapping the literary voice of Hebrew women.